Pengaruh Terapi Seni (Melukis) terhadap Fungsi Kognitif pada Pasien Skizofrenia - Khadija, Nadzira Salma Noer Khadija; Prasetyaningsih, Roh Hastuti (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Clinical manifestations in schizophrenia result in psychotic symptoms such as hallucinations, delusions, and motivational and cognitive dysfunction. Cognitive disorders in schizophrenia such as processing speed, verbal memory, visuospatial, attention, and problem solving. One form of therapy that can be applied to improve cognitive function is art therapy. Objectives: to determine the effect of art therapy (painting) on cognitive function in schizophrenia patients at the Griya PMI Peduli Rehabilitation. Methods: pre-experimental design in the form of a one group pretest-posttest design with a sample size of 30 people using purposive sampling. The instrument used in this study was Monteral Cognitive Assessment (MoCA-Ina). Results: Most of the samples were male (60.0%); the dominant age of the sample was in the early adulthood category (40.0%); the education level was dominated by Elementary Education (52.0%); more samples had non-permanent jobs (44.0%). The hypothesis test obtained a significant value of 0.000 (p<0.05), statistically there was a difference in cognitiveability before and after the intervention. Conclusion: Art therapy (painting) has an effect on the cognitive function of schizophrenia patients in the Griya PMI Peduli rehabilitation. Keywords: Art Theraphy (Painting), Cognitive Functon, Schizophrenia